Saudi Arabia : Financial System Stability Assessment: Update. (IMF Staff Country Reports; Country Report ;, 2012)
An update on Saudi Arabia's Financial System Stability Assessment (FSAP) is presented. Saudi Arabia has confronted the global financial crisis from a position of strength, and took decisive steps to manage the impact of the crisis. As a result, the financial system has weathered the crisis relatively well. The authorities have made progress implementing the recommendations of the 2004 FSAP. Many improvements have been made to bank and securities supervision. The banking sector as a whole is well capitalized and appears to be able to withstand severe temporary shocks.